Polyester Film

JP7652323B1Active Publication Date: 2025-03-27TORAY INDUSTRIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024101025
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-03-27
Estimated Expiration
2044-06-24

Smart Images

  • Figure 0007652323000001
    Figure 0007652323000001
  • Figure 0007652323000002
    Figure 0007652323000002
  • Figure 0007652323000003
    Figure 0007652323000003
Patent Text Reader

Abstract

Provided is a polyester film that exhibits excellent uniformity in elongation at temperatures equal to or higher than its glass transition temperature. [Solution] A polyester film in which, when subjected to pyrolysis gas chromatography mass spectrometry (pyrolysis GC / MS), one or more of structural formulas 1 to 3 are detected, and the peak area value per unit mass detected as structural formulas 1 to 3 is 150 to 2000 a.u. / μg.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester film having excellent uniformity of elongation at or above its glass transition temperature and excellent luminescence properties in response to excitation light of a specific wavelength. [Background technology]

[0002] Polyesters are used in a variety of industrial fields due to their ease of processing, and film-like products made from these polyesters play important roles in our daily lives, including industrial applications, optical products, packaging, and magnetic recording tapes.

[0003] Patent Document 1 discloses a polyester film made from recycled resources that contains a fluorescent whitening agent that is excited by irradiation with ultraviolet light and emits blue visible light. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2023-104955 A Summary of the Invention [Problem to be solved by the invention]

[0005] With the recent evolution of smart devices, electric vehicles, and IoT, electronic devices such as CPUs mounted on each device have rapidly increased, and accordingly, the quality of multilayer ceramic capacitors (MLCCs), which are important for driving electronic devices, is improving. The general manufacturing method of MLCCs is to use a polyester film as a base material, and a release film with a release layer on the base material, coat and laminate ceramic green sheets and electrodes on the release film, dry and harden it, peel the laminate from the release film, laminate multiple layers, and sinter it. As the quality of MLCCs improves, it is required to accurately grasp the coating positions of the ceramic green sheets and electrodes when coating, laminating, and drying them, and to laminate them, and there is a strong demand for polyester films with excellent uniformity of elongation above the glass transition temperature. Similarly, polyester films with excellent uniformity of elongation above the glass transition temperature are required for applications other than MLCCs.

[0006] However, the polyester film disclosed in Patent Document 1 has a multilayer structure having three layers, A / B / A, and further contains a fluorescent brightening agent in layer B, which may cause uneven dispersion of the fluorescent brightening agent and insufficient uniformity in elongation at or above the glass transition temperature.

[0007] Therefore, an object of the present invention is to provide a polyester film having excellent uniformity in elongation at temperatures equal to or higher than the glass transition temperature. [Means for solving the problem]

[0008] In order to solve the above problems, a preferred embodiment of the polyester film of the present invention has the following structure. (1) When pyrolysis gas chromatography mass spectrometry (pyrolysis GC / MS) was performed using the following measurement device and under the following measurement conditions, one or more of the following structural formulas 1 to 3 were detected: A polyester film having a peak area per unit mass detected as structural formulas 1 to 3 of 150 to 2000 a.u. / μg.

[0009] [ka]

[0010] [ka]

[0011] [ka]

[0012] (Measuring Equipment) Pyrolysis furnace:PY-3030iD GC:7890A MS: JMS‐Q1050GC (Measurement conditions) Pyrolysis temperature: 600℃ Column: Ultra ALLOY-5 (MS / HT) Heating conditions: Hold at 40°C for 3 minutes, then heat to 320°C at 20°C / min, and hold at 320°C for 18 minutes Inlet: 300℃ Mode: Split(20:1) 1.5mL / min constant flow Ionization method: EI+ Scan range: m / z 10,000-800,000 Scan speed: 0.5s / scan (2) 550 nm emission peak intensity with 350 nm excitation light (I 550nm ) and 370 nm emission peak intensity (I 370nm ) satisfies the following formula (i): (i) 5≦(I 550nm ) / (I 370nm )×100≦20 (3) The polyester film according to (1) or (2), wherein the content of alkali metal elements in the polyester film is 1.5 ppm by mass or more and 40.0 ppm by mass or less. (4) The polyester film according to any one of (1) to (3), wherein the alkali metal element contained in the polyester film is sodium. (5) The polyester film according to any one of (1) to (4), which is used for release purposes. Effect of the Invention

[0013] According to the present invention, it is possible to provide a polyester film having excellent uniformity in elongation at temperatures equal to or higher than the glass transition temperature. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] A preferred embodiment of the present invention will be described in detail below with reference to a specific example.

[0015] When the polyester film of the present invention is subjected to pyrolysis gas chromatography mass spectrometry (pyrolysis GC / MS) using the following measuring device and under the following measuring conditions, it is preferable that one or more of the following structural formulas 1 to 3 are detected, and the peak area value per unit mass detected as the structural formulas 1 to 3 satisfies 150 to 2000 a.u. / μg.

[0016] [ka]

[0017] [ka]

[0018] [ka]

[0019] (Measuring Equipment) Pyrolysis furnace:PY-3030iD GC:7890A MS: JMS‐Q1050GC (Measurement conditions) Pyrolysis temperature: 600℃ Column: Ultra ALLOY-5 (MS / HT) Heating conditions: Hold at 40°C for 3 minutes, then heat to 320°C at 20°C / min, and hold at 320°C for 18 minutes Mode: Split(20:1) 1.5mL / min constant flow Ionization method: EI+ Scan range: m / z 10.000-800.000 Scan speed: 0.5s / scan The Ultra ALLOY-5 (MS / HT) column is a GC capillary column manufactured by Frontier Labs, Inc., and the stationary phase is 5% diphenyldimethylpolysiloxane.

[0020] Structural formulas 1 to 3 are components having a conjugated system, and by containing the components having structural formulas 1 to 3, it is possible to obtain a polyester film that has excellent uniformity of elongation at temperatures above the glass transition temperature, leading to improved accuracy in subsequent processes. This is believed to be because structural formulas 1 to 3 are components having a conjugated system, and therefore improve stretchability regardless of the orientation of the polyester. Furthermore, it is believed that the components having structural formulas 1 to 3 are scattered among the molecular chains of the polyester, thereby mitigating restrictions on the movement of the molecular chains.

[0021] From the viewpoint of controlling the uniformity of elongation, the peak area value (au / μg) per unit mass detected as structural formulas 1 to 3 is preferably 150 or more, more preferably 500 or more, and even more preferably 1000 or more. If the peak area value (au / μg) per unit mass detected as structural formulas 1 to 3 exceeds 2000, the components having conjugation are scattered, which may cause unevenness, reduce the Young's modulus of the polyester film, make it easier to break, and deteriorate the uniformity of elongation. The detailed method of determining the peak area value will be described later.

[0022] Examples of means for achieving a peak area value per unit mass (au / μg) of 150 to 2000 detected as structural formulas 1 to 3 include a method of adding monomers consisting of structural formulas 1 to 3 and their isotopes, or oligomers or polymers having structural formulas 1 to 3 and their isotopes at repeating units or terminals. The method of addition is not particularly limited, but addition prior to the step of producing an unstretched sheet is preferred from the viewpoint of efficiently dispersing the components consisting of structural formulas 1 to 3.

[0023] The polyester film of the present invention has a 550 nm emission peak intensity (I 550nm ) and 370 nm emission peak intensity (I 370nm ) preferably satisfies the following formula (i). (i) 5≦(I 550nm ) / (I 370nm )×100≦20 (I 550nm ) / (I 370nm )×100 is 5 or more and 20 or less, when the polyester film is irradiated with black light, the components consisting of structural formulas 1 to 3 have good luminescence in the visible light region, and may be preferably used for appearance inspection purposes. In particular, when a release layer or a layer of a release target is provided, it becomes difficult to detect transmitted light, so that excellent luminescence in the visible light region may be more preferably used. From the viewpoint of preventing detection omissions in inspection purposes, (I 550nm ) / (I 370nm ) × 100 is preferably 5 or more, more preferably 10 or more, and even more preferably 20 or more. 550nm ) / (I 370nm )×100 exceeds 20, the emission peak intensity is high and the emission position may become unclear, which is not preferable. The method for measuring the emission peak intensity will be described later. Examples of means for satisfying formula (i) include a method of adding a monomer consisting of the above structural formulas 1 to 3 and their isotopes, or an oligomer or polymer having structural formulas 1 to 3 and their isotopes in a repeating unit or at a terminal.

[0024] The amount of alkali metal element contained in the polyester film of the present invention is preferably 1.5 mass ppm or more and 40.0 mass ppm or less. When the amount of alkali metal element is within the preferred range, the hydrophilic part and the hydrophobic part of the polyester film are uniformly dispersed, and the affinity between the component consisting of structural formulas 1 to 3 and the hydrophobic part is increased, and scattering due to heat may be suppressed, or the dispersibility of the component consisting of structural formulas 1 to 3 may be easily controlled, and for example, the applicability of the release agent may be excellent. If the amount of alkali metal element contained in the polyester film is less than 1.5 mass ppm, the dispersibility of the component consisting of structural formulas 1 to 3 may become uneven, which may be undesirable. If the amount of alkali metal element contained in the polyester film exceeds 40.0 mass ppm, the component having a conjugated system may be scattered, and when used as a process release film, defects may occur when applying the release target, which may be undesirable from the viewpoint of quality stability. The amount of alkali metal element contained in the polyester film is more preferably 3.0 mass ppm or more and 30.0 mass ppm or less, and even more preferably 6.0 mass ppm or more and 20.0 mass ppm or less.

[0025] Preferred examples of the alkali metal element contained in the polyester film of the present invention include lithium, sodium, potassium, rubidium, cesium, and francium, of which sodium is more preferred from the viewpoints of versatility and ease of handling.

[0026] The method for incorporating an alkali metal element into the polyester film of the present invention is not particularly limited, and may be a method of adding an alkali metal compound during the polymerization process or film-forming process of the polyester film, or a method of contacting the polyester film with an aqueous solution containing an alkali metal element.

[0027] The polyester film of the present invention refers to a film containing polyester as a main component, where the main component means a component contained in the film in an amount of more than 50% by mass, where the total components of the film are 100% by mass.

[0028] The polyester in the present invention is a material having a dicarboxylic acid component and a diol component. In this specification, the component refers to the smallest unit obtainable by hydrolysis of the polyester. Examples of the dicarboxylic acid component constituting such a polyester include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, and 4,4'-diphenyletherdicarboxylic acid. In addition, the polyester film of the present invention preferably contains terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, and 4,4'-diphenyletherdicarboxylic acid in total at 95 mol% or more, and more preferably at 99 mol% or more, of 100 mol% of the acid component of the polyester.

[0029] Examples of diol components constituting such polyesters include aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,2-butanediol, and 1,3-butanediol; alicyclic diols such as cyclohexanedimethanol and spiroglycol; and diols in which a plurality of the above-mentioned diols are linked together.

[0030] In terms of mechanical properties and transparency, the polyesters used in the present invention are preferably polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene-2,6-naphthalenedicarboxylate (PEN), and polyesters obtained by copolymerizing a part of the dicarboxylic acid component of PET with isophthalic acid or naphthalenedicarboxylic acid, and polyesters obtained by copolymerizing a part of the diol component of PET with cyclohexanedimethanol, spiroglycol, or diethylene glycol, and among these, polyethylene terephthalate and polyethylene-2,6-naphthalenedicarboxylate are particularly preferred. That is, the polyester film of the present invention preferably has an aromatic ring, and is preferably a film of polyethylene terephthalate (PET), polybutylene terephthalate (PBT), or polyethylene-2,6-naphthalenedicarboxylate (PEN), and more preferably a polyethylene terephthalate film. In addition, these PET, PBT, and PEN may contain a copolymerization component.

[0031] The polyester can be produced by a known method, and it is preferable to use a polyester having an intrinsic viscosity in the range of 0.50 to 0.80 dl / g. More preferably, it is in the range of 0.50 to 0.75 dl / g, and even more preferably, it is in the range of 0.50 to 0.70 dl / g. The intrinsic viscosity is measured using a value calculated from the solution viscosity measured in orthochlorophenol at 25°C using the following formula. ηsp / C=[η]+K[η] 2 C Here, ηsp = (solution viscosity / solvent viscosity)-1, C is the mass of polymer dissolved per 100 ml of solvent (g / 100 ml, usually 1.2), and K is the Huggins constant (0.343). The solution viscosity and solvent viscosity are measured using an Ostwald viscometer. The unit is [dl / g].

[0032] The polyester film of the present invention is preferably a biaxially oriented polyester film. Biaxial orientation in the present invention means a film that shows a biaxially oriented pattern in wide-angle X-ray diffraction. The polyester film can be obtained by stretching an unstretched (unoriented) film in two-dimensional directions by a conventional method. The stretching can be either a sequential biaxial stretching method or a simultaneous biaxial stretching method. In the sequential biaxial stretching, the steps of stretching in the longitudinal direction (vertical) and the width direction (horizontal) can be performed once each in the longitudinal direction and once each in the transverse direction, or twice each in the longitudinal direction-horizontal-vertical-horizontal direction, for example.

[0033] The polyester film of the present invention may contain inorganic particles or organic particles, or both, as long as the characteristics of the present invention are not impaired. Examples of inorganic particles include calcium carbonate, magnesium carbonate, zinc carbonate, titanium oxide, zinc oxide, cerium oxide, magnesium oxide, barium sulfate, zinc sulfide, calcium phosphate, alumina (α-alumina, β-alumina, γ-alumina, δ-alumina), mica, mica titanium, zeolite, talc, clay, kaolin, lithium fluoride, calcium fluoride, montmorillonite, zirconia, wet silica, dry silica, and colloidal silica. Examples of organic particles include organic particles containing acrylic resins, styrene resins, silicone resins, polyimide resins, and core-shell organic particles.

[0034] The thickness of the polyester film of the present invention is not particularly limited, but is preferably 10 μm to 300 μm. More preferably, it is 12 μm to 100 μm, and even more preferably, it is 14 μm to 50 μm. If the thickness is less than 10 μm, the rigidity is insufficient, and there is a concern that the film may break more frequently during the film formation process. Furthermore, when the film is used as a molding substrate for MLCC, there is a risk of film breakage or coating unevenness (film thickness unevenness) due to film stretching during the production of ceramic green sheets.

[0035] The polyester film of the present invention may have a single layer, two layers, or three or more layers. In the case of two layers, it is composed of a polyester A layer and a polyester B layer, and in the case of three layers, it is a laminated film composed of three layers, namely, a polyester A layer, a polyester B layer, and a polyester C layer, or a polyester A layer, a polyester B layer, and a polyester A layer. In the case of a laminated film composed of three layers, A layer / B layer / C layer, or a laminated film composed of three layers, A layer / B layer / A layer, A layer is a layer suitable for forming a surface on which a release layer or a release target is applied, C layer is a layer suitable for forming the opposite surface of the release layer, and B layer is a layer located between A layer and C layer or between A layer and A layer (hereinafter, sometimes referred to as an intermediate layer). In addition, pre-consumer materials generated from the waste route of the edge part of the film generated in the film production process, recycled materials obtained by regenerating in-house recycled materials generated from the waste route of other film production processes, and post-consumer materials can also be mixed into the intermediate layer within a range that does not adversely affect the properties of the film surface. The blend ratio may be such that the material is made only from recycled materials such as release films that are discarded after being used as products, or the recycled materials may be appropriately mixed with other raw materials, which can provide cost benefits.

[0036] Next, a method for producing the polyester film of the present invention will be described, but the present invention is not limited to the products obtained by such examples.

[0037] The polyester used in the present invention can be obtained by a conventional polymerization method. For example, a dicarboxylic acid component such as terephthalic acid or its ester-forming derivative and a diol component such as ethylene glycol or its ester-forming derivative are transesterified or esterified by a known method, followed by melt polymerization. If necessary, the polyester obtained by the melt polymerization reaction can be subjected to solid-phase polymerization at a temperature below the melting point of the polyester.

[0038] The polyester film of the present invention can be obtained by a conventionally known production method, but by producing the film under the following conditions for the stretching and heat treatment steps, at least one side of the film can be made to have the above-mentioned preferable physical properties.

[0039] The polyester film of the present invention contains the components represented by the structural formulae 1 to 3. The method for incorporating the components represented by the structural formulae 1 to 3 can be any method known in the art. In particular, when the components represented by the structural formulae 1 to 3 are added before the step of producing an unstretched sheet, the components can be well dispersed in some cases.

[0040] The polyester film of the present invention can be produced by a method (melt casting method) in which dried raw materials are heated and melted in an extruder as necessary, and extruded from a die onto a cooled cast drum to be processed into a sheet. When a polyester film having two or more layers is produced by the melt casting method, an extruder is used for each layer constituting the polyester film, and the raw materials of each layer are melted and filtered through a filter. Even very small foreign matter can become a coarse protrusion defect if it enters the polyester film, so it is effective to use a high-precision filter that captures 95% or more of foreign matter of 3 μm or more. Next, the melted raw materials are laminated in a molten state in a merging device, and then introduced into a die, and extruded from the die onto a cast drum to be processed into a sheet (co-extrusion method). The sheet is preferably cooled and solidified by static electricity on a drum whose surface temperature is cooled to 20° C. or more and 60° C. or less to produce an unstretched sheet. The temperature of the cast drum is more preferably 20° C. or more and 40° C. or less, and even more preferably 20° C. or more and 30° C. or less. If the temperature exceeds 60° C., the film may stick to the casting drum, making it difficult to obtain an unstretched sheet.

[0041] Next, as the conditions for longitudinal stretching when the unstretched film is biaxially stretched, it is preferable to introduce the unstretched film into a roll group heated to 70°C or more, stretch it in the longitudinal direction, and cool it with a roll group set at a temperature of 20°C to 50°C. The lower limit of the heating roll temperature in the longitudinal stretching is not particularly limited as long as it does not impair the stretchability of the sheet, but it is preferable that the heating roll temperature exceeds the glass transition temperature of the polyester resin used. In addition, the preferred range of the longitudinal stretching ratio is 3 times or more and 5 times or less. A more preferred range is 3 times or more and 4 times or less. When the longitudinal stretching ratio is 3 times or more, orientation crystallization proceeds and the film strength can be improved. On the other hand, by setting the stretching ratio to 5 times or less, the orientation crystallization of the polyester resin accompanying stretching proceeds excessively, making the film brittle, and the occurrence of breakage during film formation can be suppressed. A method using the speed difference between rolls is preferably used as a method for stretching the film in the longitudinal direction. In this case, it is also a preferred embodiment to stretch the film in a plurality of sections while fixing the film with nip rolls to prevent the film from slipping. The stretching speed in the longitudinal direction is preferably 5,000% / min or more and 100,000% / min or less.

[0042] Next, for stretching in the direction perpendicular to the longitudinal direction (width direction), the film is introduced into a tenter while holding both ends with clips, and is preferably stretched 3 to 5 times in the direction perpendicular to the longitudinal direction (width direction) in an atmosphere heated to a temperature of 70 to 160°C, and then the stretched film is heat-treated to stabilize the internal orientation structure. The heat history temperature of the film during heat treatment can be confirmed by the temperature of a minute endothermic peak (sometimes called Tmeta) that appears just below the melting point temperature measured by a differential scanning calorimeter (DSC) described later. When polyester (melting point 255°C) is the main component, the tenter device setting temperature is preferably set so that the maximum temperature in the tenter is 200 to 250°C, and when other thermoplastic resins are the main component, it is preferably set to the resin melting point -55°C or less, or resin melting point -5°C or less. By setting the heat treatment temperature at 200° C. or higher, the dimensional stability of the biaxially oriented polyester film can be improved, and by setting the heat treatment temperature at 250° C. or lower, the occurrence of film breakage due to melting of the polyester film can be suppressed, and production can be performed with good productivity. A more preferred range is 220° C. or higher and 245° C. or lower.

[0043] For the reasons mentioned above, the range of Tmeta, which represents the heat history temperature of the film during heat treatment, is preferably 190°C or more and 245°C or less when the main component is polyester resin, and more preferably 210°C or more and 240°C or less.

[0044] Furthermore, in order to impart dimensional stability after the heat treatment, a relaxation treatment may be performed in the range of 1% to 6%. A relaxation treatment of 1% or more can improve the dimensional stability when the polyester film is used in a high-temperature environment, while a relaxation treatment of 6% or less can keep the polyester film under an appropriate tension and prevent thickness unevenness from worsening.

[0045] The stretching ratio is 3 times or more and 5 times or less in both the longitudinal direction and the width direction, and the area ratio (stretching ratio in the longitudinal direction x stretching ratio in the width direction) is preferably 9 times or more and 22 times or less, and more preferably 9 times or more and 20 times or less. By setting the area ratio to 9 times or more, the molecular orientation of the polyester film obtained can be promoted and durability can be improved, and by setting the area ratio to 22 times or less, the occurrence of breakage during stretching can be suppressed. In addition, the stretching ratio (stretching ratio in the longitudinal direction / stretching ratio in the width direction) is preferably 0.6 times or more and 1.7 times or less, more preferably 0.7 times or more and 1.5 times or less, and even more preferably 0.8 times or more and 1.3 times or less. By setting the stretching ratio to 0.6 times or more and 1.7 times or less, the molecular orientation of the polyester film obtained can be controlled, and uniform elongation can be achieved even at or above the glass transition temperature.

[0046] For example, when producing a release film, the polyester film of the present invention is coated with a release agent and cured by heat treatment. Since the polyester film shrinks and stretches due to the tension of heat treatment and transport, the polyester film of the present invention has less unevenness in the release layer and can be preferably used for release purposes. In addition, the film of the present invention is provided with a release layer on at least one side, and can also be preferably used for appearance inspection purposes after providing a release layer on the release layer. For example, This is because the detection accuracy of the defect position of the solid electrolyte is good if the support is used for producing a solid electrolyte of a battery. Note that the solid electrolyte also includes semi-solid electrolytes that contain liquids or gels.

[0047] <Characteristics evaluation method> A. Evaluation by pyrolysis GC / MS Approximately 100 μg of the polyester film is sampled and freeze-pulverized to obtain a powdered sample, which is then subjected to pyrolysis GC / MS measurement under the following conditions. (Measuring Equipment) Pyrolysis furnace:PY-3030iD GC:7890A MS:JMS-Q1050GC (Measurement conditions) Pyrolysis temperature: 600℃ Column: "Ultra ALLOY" (registered trademark)-5 (MS / HT) Heating conditions: Hold at 40°C for 3 minutes, then heat to 320°C at 20°C / min, and hold at 320°C for 18 minutes Mode: Split(20:1) 1.5mL / min constant flow Ionization method: EI+ Scan range: m / z 10.000-800.000 Scan speed: 0.5s / scan.

[0048] (i) Peak area per unit mass The peak area value per unit mass (au / μg) is calculated by dividing the sum of the peak areas detected as structural formulas 1 to 3 by the mass of the sample used, assuming that the maximum peak intensity value for the obtained chromatogram is 100. Here, the peak area value per unit mass is the arithmetic average value of the sample sampled at any two points.

[0049] B. Evaluation by Emission Spectrum Measurement A polyester film is laid out and the emission spectrum is measured under the following conditions. The emission intensity is normalized by the excitation light intensity of each wavelength. The wavelength dependency of the detection sensitivity of the spectrometer is also corrected, and dark count correction is also performed. (Measurement conditions) Equipment: Horiba Jobin Yvon Fluorolog3-22 Light source: Xenon lamp Detector: PMT Excitation wavelength: 350 nm Observation wavelength: ~750nm (2nm intervals) Excitation side slit width: 2 nm Observation side slit width: 2 nm Time constant: 0.2s Measurement mode: Sc / Rc Observation position: 22.5° to the excitation light (i) Emission peak intensity From the obtained emission spectrum, the emission peak intensity at each wavelength is determined.

[0050] (ii) Luminescence The value calculated by the following formula is regarded as luminescence. Luminescence = (I 550nm ) / (I 370nm ) x 100 Here, I 550nm is the emission peak intensity at 550 nm, I 370nm is the emission peak intensity at 370 nm. The luminescence is evaluated according to the following criteria. A: 15 or more B: 10 to 15 C: 5 or more and less than 10 D: Less than 5 C. Evaluation by thermostatic Tensilon above the glass transition temperature The polyester film is cut into a rectangular sample of 150 mm in length and 10 mm in width at any position in the longitudinal and transverse directions. Using a tensile tester (Orientec "Tensilon" (registered trademark) UCT-100), a tensile test is performed in the longitudinal and transverse directions of the polyester film with an initial tensile chuck distance of 50 mm and a tensile speed of 300 mm / min to determine the Young's modulus and breaking elongation. The sample is placed in a thermostatic chamber previously set to 100°C, and after preheating for 90 seconds, a tensile test is performed in air.

[0051] (i) Young’s modulus The tensile Young's modulus is calculated from the tangent to the rising part of the obtained load-elongation curve. The measurement is carried out 10 times for each sample, and the average value of the obtained values ​​is used.

[0052] (ii) Breaking elongation The value calculated by the following formula is defined as the breaking elongation. Elongation at break (%) = 100 × (LL 0 ) / L 0 Here, L 0 is the length of the sample before the test (mm), and L is the length of the sample at the time of fracture.

[0053] (iii) Elongation uniformity Elongation uniformity is evaluated by the coefficient of variation (standard deviation / average value) of breaking elongation. Measurements are performed 10 times for each sample, and the coefficient of variation of breaking elongation is calculated. The lower the coefficient of variation of breaking elongation, the less variation there is, which is preferable because it leads to improved accuracy in subsequent processes.

[0054] D. Atomic absorption spectrometry The alkali metal elements are quantified by atomic absorption spectrometry (polarized Zeeman atomic absorption spectrometer 180-80, manufactured by Hitachi, Ltd.; flame: acetylene-air).

[0055] E. Thickness of each layer When the polyester film is a laminated film, the thickness of each layer is measured by the following method. A cross section of the film is cut out with a microtome in a direction parallel to the width direction of the film. The cross section is observed with a scanning electron microscope at a magnification of 5000 times, and the thickness of each laminated layer is measured.

[0056] F. Intrinsic viscosity (IV) A measurement sample (polyester resin (raw material)) is dissolved in 100 ml of orthochlorophenol (solution concentration C (measurement sample weight / solution volume) = 1.2 g / 100 ml), and the viscosity of the solution at 25°C is measured using an Ostwald viscometer. The viscosity of the solvent is also measured in the same manner. Using the solution viscosity and solvent viscosity thus obtained, [η] is calculated according to the following formula (1), and the obtained value is regarded as the intrinsic viscosity (IV). ηsp / C=[η]+K[η] 2 ·C··(1) (Here, ηsp = (solution viscosity / solvent viscosity)-1, and K is the Huggins constant (assumed to be 0.343).) If the solution in which the measurement sample is dissolved contains insoluble matter such as inorganic particles, the measurement is carried out using the following method. (1-1) Dissolve the measurement sample in 100 mL of orthochlorophenol to prepare a solution with a concentration of more than 1.2 g / 100 mL. The weight of the measurement sample provided in orthochlorophenol is the measurement sample weight. (1-2) Next, the solution containing the insoluble matter is filtered, and the weight of the insoluble matter and the volume of the filtrate after filtration are measured. (1-3) Add orthochlorophenol to the filtrate after filtration to adjust the ratio (weight of measured sample (g) - weight of insoluble matter (g)) / (volume of filtrate after filtration (mL) + volume of added orthochlorophenol (mL)) to 1.2 g / 100 mL. (For example, when a concentrated solution with a measurement sample weight of 2.0 g / solution volume of 100 mL is prepared, if the weight of the insoluble matter when the solution is filtered is 0.2 g and the volume of the filtrate after filtration is 99 mL, an adjustment is made by adding 51 mL of orthochlorophenol. ((2.0 g-0.2 g) / (99 mL+51 mL)=1.2 g / 100 mL)) (1-4) Using the solution obtained in (1-3), measure the viscosity at 25°C using an Ostwald viscometer, and use the obtained solution viscosity and solvent viscosity to calculate [η] according to the above formula (1), and the obtained value is regarded as the intrinsic viscosity (IV).

[0057] G. Melting point of polyester film Tm (℃) The measurement samples are measured according to the method based on JIS K 7121 (1987) using a differential scanning calorimeter "Robot DSC-RDC220" manufactured by Seiko Denshi Kogyo Co., Ltd., and a Disk Session "SSC / 5200" for data analysis, as follows.

[0058] Weigh out 5 mg of a sample into a sample pan, heat the sample from 25°C to 300°C at a heating rate of 10°C / min, and obtain a differential scanning calorimetry chart for the first run. Determine the peak temperature of the endothermic peak in the differential scanning calorimetry chart for the first run, and define it as Tm (°C).

[0059] H. Pinhole evaluation 100 parts by mass of barium titanate (manufactured by Fuji Titanium Industries Co., Ltd. under the trade name of HPBT-1), 10 parts by mass of polyvinyl butyral (manufactured by Sekisui Chemical Co., Ltd. under the trade name of BL-1), 5 parts by mass of dibutyl phthalate, and 60 parts by mass of toluene-ethanol (mass ratio 30:30) are added with glass beads having a number average particle size of 2 mm, mixed and dispersed for 20 hours using a jet mill, and then filtered to prepare a paste-like dielectric paste. The obtained dielectric paste is applied to a release film with a die coater so that the thickness after drying is 2 μm, dried, and wound up to obtain a ceramic green sheet with a release film. The wound ceramic green sheet is unrolled and visually observed without being peeled off from the release film to check for the presence or absence of pinholes. The observation area is 300 mm wide and 500 mm long. The ceramic green sheet molded on the release film is observed for pinholes while being illuminated from the back with a 1000 lux backlight unit, and is evaluated as follows. A: 3 or fewer pinholes. B: 4 to 6 pinholes. C: 7 to 9 pinholes. D: 10 or more pinholes.

[0060] I. Particle size The average particle size is determined by the equivalent spherical diameter of the particle at the 50% volume point measured using an electron micrograph of the particle. The equivalent spherical diameter is the diameter of a sphere having the same volume as the particle.

[0061] J. Particle thermal decomposition temperature Using a Rigaku Denki TAS-100, measure the thermobalance weight loss curve at a heating rate of 20℃ / min in a nitrogen atmosphere. The temperature at which 10% weight loss occurs is taken as the thermal decomposition temperature. EXAMPLES

[0062] The present invention will be described below with reference to examples, but the present invention is not necessarily limited to these.

[0063] [Production of PET-1] Terephthalic acid and ethylene glycol were polymerized in the usual manner using antimony trioxide and magnesium acetate tetrahydrate as catalysts to obtain melt-polymerized PET. The resulting melt-polymerized PET-1 had a glass transition temperature of 81°C, a melting point of 255°C, an intrinsic viscosity of 0.65, and a terminal carboxyl group content of 20 eq. / t.

[0064] [Production of Particle A] Seed particles made of polystyrene were synthesized by emulsion polymerization of vinylbenzene and methacrylic acid in a conventional manner. The seed particles, vinylbenzene, divinylbenzene, and methacrylic acid were then subjected to emulsion polymerization using sodium peroxide as a polymerization initiator to obtain particles A made of a divinylbenzene-styrene crosslinked structure. The particle size of particles A was 0.4 μm, and the thermal decomposition temperature was 400°C.

[0065] [Preparation of Coating A] Coating agent A was obtained by mixing 100 parts by mass of an addition reaction type silicone resin release agent (manufactured by Shin-Etsu Chemical Co., Ltd. under the product name KS-847T) and 1 part by mass of a platinum catalyst (manufactured by Shin-Etsu Chemical Co., Ltd. under the product name CAT-PL-50T) in toluene as a solvent to give a solids content of 1.5% by mass.

[0066] [Preparation of dielectric paste] Glass beads having a number average particle size of 2 mm were added to 100 parts by mass of barium titanate (manufactured by Fuji Titanium Kogyo Co., Ltd., product name HPBT-1), 10 parts by mass of polyvinyl butyral (manufactured by Sekisui Chemical Co., Ltd., product name BL-1), 5 parts by mass of dibutyl phthalate, and 60 parts by mass of toluene-ethanol (mass ratio 30:30), and the mixture was mixed and dispersed in a jet mill for 20 hours, and then filtered to produce a dielectric paste in paste form.

[0067] Example 1 PET-1 was vacuum-dried at 160°C for 2 hours, and then 0.10 mass% each of the components represented by structural formulas 1 to 3 was added and stirred. The mixture was then placed in an extruder, melted at 280°C, and extruded through a die onto a casting drum with a surface temperature of 25°C to produce an unstretched sheet.

[0068] The sheet was then preheated with a group of heated rolls, stretched 3.8 times in the longitudinal direction at a temperature of 90°C, and then cooled with a group of rolls at a temperature of 25°C to obtain a uniaxially stretched film. The obtained uniaxially stretched film was stretched 4.0 times in the width direction perpendicular to the longitudinal direction in a heating zone at a temperature of 100°C in a tenter while both ends of the film were held with clips. Further, the sheet was heat-set for 10 seconds at a temperature of 230°C in a heat treatment zone in the tenter. Next, the sheet was uniformly cooled in a cooling zone and then wound up to obtain a polyester film having a thickness of 31 μm.

[0069] Coating agent A was applied to one side of the obtained polyester film by gravure coating so that the coating thickness after drying would be 100 nm, and a release film was obtained. Dielectric paste was applied to the obtained release film as the release material by die coating so that the thickness after drying would be 1.0 μm, and the film was dried and wound up to obtain a ceramic green sheet. The evaluation results are shown in the table.

[0070] [Production of PET-2] The polyester film obtained in Example 1 was pulverized in a grinder to produce flakes, which were then stirred in an aqueous alkali solution containing sodium as an alkali metal element for 5 minutes. The flakes were vacuum dried, then fed into an extruder equipped with vent holes, and kneaded while maintaining a reduced pressure of 1 kPa or less to remove moisture, to obtain PET-2. The glass transition temperature of PET-2 was 78°C, the melting point was 253°C, the intrinsic viscosity was 0.60, and the amount of terminal carboxyl groups was 37 eq. / t.

[0071] [Production of PET-3] The polyester film obtained in Example 1 was pulverized in a grinder to produce flakes, which were then stirred in an aqueous alkali solution containing sodium as an alkali metal element for 2 minutes. The flakes were vacuum dried, then fed into an extruder equipped with vent holes, and kneaded while maintaining a reduced pressure of 1 kPa or less to remove moisture, to obtain PET-3. The glass transition temperature of PET-3 was 79°C, the melting point was 253°C, the intrinsic viscosity was 0.60, and the amount of terminal carboxyl groups was 38 eq. / t.

[0072] [Production of PET-4] PET-1 was vacuum dried at 160°C for 2 hours, then put into an extruder, melted at 280°C, and extruded through a die onto a casting drum with a surface temperature of 25°C to produce an unstretched sheet. The sheet was then preheated with a heated roll group, stretched 3.8 times in the longitudinal direction at a temperature of 90°C, and then cooled with a roll group at a temperature of 25°C to obtain a uniaxially stretched film. The obtained uniaxially stretched film was stretched 4.0 times in the width direction perpendicular to the longitudinal direction in a heating zone at a temperature of 100°C in a tenter while holding both ends of the film with clips. Further, the film was heat-set for 10 seconds at a temperature of 230°C in a heat treatment zone in the tenter. Next, the film was uniformly cooled slowly in a cooling zone, and then wound up to obtain a polyester film with a thickness of 31 μm. The polyester film was pulverized with a grinder to produce flakes, which were then vacuum dried, and then put into an extruder with a vent hole, and kneaded while maintaining a reduced pressure of 1 kPa or less to remove moisture, to obtain PET-4. The glass transition temperature of PET-4 was 78°C, the melting point was 253°C, the intrinsic viscosity was 0.60, and the amount of terminal carboxyl groups was 39 eq. / t.

[0073] [Production of PET-5] PET-1 and Particle A were fed into an extruder with vent holes so that Particle A was present at 1.0% by mass relative to PET-5, and kneaded while removing moisture under a reduced pressure of 1 kPa or less to obtain PET-5. The glass transition temperature was 81°C, the melting point was 255°C, the intrinsic viscosity was 0.61, and the amount of terminal carboxyl groups was 22 eq. / t.

[0074] [Production of PET-6] PET-6 was produced in the same manner as PET-4, except that PET-1 was changed to PET-5. PET-6 had a glass transition temperature of 79°C, a melting point of 252°C, an intrinsic viscosity of 0.60, and a terminal carboxyl group content of 28 eq. / t.

[0075] (Examples 2 to 6) Polyester films were prepared in the same manner as in Example 1, except that the amounts of the components represented by Structural Formulas 1 to 3 added were changed as shown in the table.

[0076] (Examples 7 to 12) Polyester films were prepared in the same manner as in Examples 1 to 6, except that PET-1 was changed to PET-2.

[0077] Example 13 A polyester film was prepared in the same manner as in Example 1, except that PET-1 was changed to PET-3.

[0078] Comparative Example 1 A polyester film was prepared in the same manner as in Example 1, except that the components represented by Structural Formulas 1 to 3 were not added.

[0079] Comparative Example 2 A polyester film was prepared in the same manner as in Comparative Example 1, except that PET-1 was changed to PET-4.

[0080] Comparative Example 3 A polyester film was prepared in the same manner as in Comparative Example 1, except that PET-1 was changed to PET-5.

[0081] Comparative Example 4 A polyester film was prepared in the same manner as in Comparative Example 1, except that PET-1 was changed to PET-6.

[0082] Comparative Example 5 Polyester films were prepared in the same manner as in Example 1, except that the amounts of the components represented by Structural Formulas 1 to 3 added were changed as shown in the table.

[0083] [Table 1]

[0084] [Table 2]

[0085] [Table 3]

[0086] [Table 4]

[0087] In Examples 1 to 13, the peak area per unit mass in pyrolysis GC / MS evaluation was within a preferred range, and thus polyester films with excellent elongation uniformity and luminescence were obtained. In particular, in Examples 7 to 13, the components represented by Structural Formulas 1 to 3 were uniformly dispersed by contact with an aqueous solution containing an alkali metal element, and therefore the release layer had excellent coatability and pinhole evaluation.

[0088] In Comparative Examples 1 to 4, the peak area value per unit mass in the pyrolysis GC / MS evaluation was less than 150, and therefore the uniformity of elongation was poor and the luminescence was inferior. In Comparative Example 5, the peak area value per unit mass in the pyrolysis GC / MS evaluation exceeded 2000, and therefore the polyester film was easily broken and the uniformity of elongation was uneven. [Industrial Applicability]

[0089] The polyester film of the present invention has excellent uniformity of elongation at or above the glass transition temperature, and therefore can be suitably used for release purposes from the viewpoint of uniform application of a release agent. In addition, the polyester film has excellent luminescence properties with respect to excitation light of a specific wavelength, and therefore can be suitably used for appearance inspection purposes.

Claims

1. When pyrolysis gas chromatography mass spectrometry (pyrolysis GC / MS) was performed using the following measurement device and under the following measurement conditions, any one or more of the following structural formulas 1 to 3 was detected: A polyester film having a peak area per unit mass detected as structural formulas 1 to 3 of 150 to 2000 a.u. / μg. 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 (Measuring device) Pyrolysis furnace: PY-3030iD GC: 7890A MS: JMS-Q1050GC (Measurement conditions) Thermal decomposition temperature: 600℃ Column: Ultra ALLOY-5 (MS / HT) Heating conditions: hold at 40°C for 3 minutes, then heat to 320°C at 20°C / min, and hold at 320°C for 18 minutes Inlet: 300℃ Mode: Split (20:1) 1.5mL / min constant flow Ionization method: EI+ Scan range: m / z 10,000 to 800,000 Scan speed: 0.5 s / scan

2. 2. The polyester film according to claim 1, wherein the content of an alkali metal element in the polyester film is from 1.5 ppm by mass to 40.0 ppm by mass.

3. 3. The polyester film according to claim 1, wherein the alkali metal element contained in the polyester film is sodium.

4. 3. The polyester film according to claim 1, which is used for releasing purposes.

Citation Information

Patent Citations

  • Biaxially oriented polyester film

    JP1994271750A

  • Polyester composition

    JP1995233312A

  • Release polyester film

    JP2013007054A

  • Recycled resources-derived polyester film and method for producing the same

    JP2023104955A

  • Method for manufacturing recycled polyester film and method for manufacturing recycled polyester resin chips

    JP2024010650A